A systems approach to public administration and social equity - Pooser, Todd (Public administration & social equity., 2024)
"A Systems Approach to Public Administration uses General Systems Theory - a cross-disciplinary scientific philosophy first articulated by Ludwig von Bertalanffy then refined by Ervin Laszlo, and covering fields that include but are not limited to human psychology, cell biology, evolutionary biology, linguistics, the theory of consciousness and the human mind, and physics - to formulate "The Plan": a series of social policies that if enacted, will enable all of humanity to live in the best possible world given the conditions of our existence. The notion that human society faces a series of unprecedented threats is no longer the purview of those wearing tinfoil hats or walking down Broadway with a sandwich board declaring "The End Is Nigh." We are at a crossroads after which is, in all likelihood, the point of no return. The Plan transcends common, high-level platitudes to advance series of Public Private Trusts - Energy, Resource, Agriculture, Transportation, Health and Technology - in which members invest and become equity partners to create a "Virtual Commonwealth." In so doing, we leverage our significant population, tax revenue and disposable income majorities to directly and immediately steer the political economy towards a sustainable, equitable, healthy future for everyone. At each step, I show how The Plan reflects the moral philosophy set forth in the first half of the book, one grounded in an incontrovertible cross-disciplinary science that describes not just the underlying nature of the universe, but our relationship to the infinite. More than just a plan of action to address the problems related to human survival and physical security, my book articulates a vision of humanity's redemption, whereby we all become more unique, purposeful and fulfilled individuals by accepting responsibility not only for our own well-being, but the well-being of others and the world of which we are a part. It is an uplifting, empowering vision of love and understanding grounded in the scientific fact that all living systems - from the simplest or organisms to the most complex of human societies - are quite literally part of one another, both physically and informationally"--